A synthetic homeodomain binding site acts as a cell type specific, promoter specific enhancer in Drosophila embryos. - Vincent, J P (1990)
A DNA sequence initially defined as a consensus binding site for the Engrailed protein is also recognized by several other homeodomain proteins and mediates the transcriptional action of these regulators in transfected tissue culture cells. Here we show that these synthetic binding sites have a more restricted and specific ability to enhance transcription when assayed in transformed embryos. Several constructs with the homeodomain binding sites linked to the fushi tarazu or engrailed promoters are silent in transformed embryos. However, when linked to the hsp70 promoter, the sites specifically activate transcription in glial cells. The effect of single base pair mutations in the binding sites suggests that activation is mediated by homeodomain protein(s). We suggest that this specific pattern of expression results from combined action at sequences within the hsp70 promoter fragment and the homeodomain binding sites. Since the tissue culture transfection assay does not show such rigid constraints on promoter activation by homeodomain proteins, it appears that subsidiary phenomena apparent in the transgenic embryos contribute importantly to the specificity of action of functionally homologous homeodomain regulators.